Heterogeneity in Returns to Investment in Education in Egypt - Herrera, Santiago; Badr, Karim (World Scientific, 2013)
The paper estimates the rates of return to investment in education in Egypt, allowing for multiple sources of heterogeneity across individuals. The paper finds that, in the period 1998–2006, returns to education increased for workers with higher education, but fell for workers with intermediate education levels; the relative wage of illiterate workers also fell in the period. This change can be explained by supply and demand factors. On the supply side, the number workers with intermediate education, as well as illiterate ones, outpaced the growth of other categories joining the labor force during the decade. From the labor demand side, the Egyptian economy experienced a structural transformation by which sectors demanding higher-skilled labor, such as financial intermediation and communications, gained importance to the detriment of agriculture and construction, which demand lower-skilled workers. In Egypt, individuals are sorted into different educational tracks, creating the first source of heterogeneity: those that are sorted into the general secondary-university track have higher returns than those sorted into vocational training. Second, the paper finds that large-firm workers earn higher returns than small-firm workers. Third, females have larger returns to education. Female government workers earn similar wages as private sector female workers, while male workers in the private sector earn a premium of about 20 percent on average. This could lead to higher female reservation wages, which could explain why female unemployment rates are significantly higher than male unemployment rates. Formal workers earn higher rates of return to education than those in the informal sector, which did not happen a decade earlier. And finally, those individuals with access to technology (as proxied by personal computer ownership) have higher returns.